The anti-venom potential of Andrographis paniculata (Burm.f.) Nees roots and its constituent skullcapflavone I - Maria Carmen S. Tan, Raymond S. Malabed , Francisco C. Franco Jr., Yves Ira A. Reyes, Daisylyn Senna Tan, Glenn G. Oyong, Chien-Chang Shen, Consolacion Y. Ragasa (Journal of Applied Pharmaceutical Science, 2019)
The anti-venom activity of Andrographis paniculata (Burm.f.) Nees roots (APR) dichloromethane crude extracts and a promising APR constituent, skullcapflavone I (SKI) was investigated by monitoring the inhibition of secretory phospholipase A2 (sPLA2) of Naja philippinensis Taylor venom (NPV) crystallized samples. Gas chromatography-mass spectrometry was used for the characterization of extracts, while molecular docking was utilized to understand anti-venom properties. Chromatographic analyses primarily revealed the presence of methoxylated flavones. NPV was found to have sPLA2 activity (0.0796 ± 0.0018 μmol/minutes/ml) that has been attributed to the poisonous effects. SKI (IC50: 51.1 ± 3.5 μg/ml), isolated from APR showed strong inhibitory effect on phospholipase activity compared with dichloromethane extracts of APR (IC50: 192.7 ± 10.9 μg/ml) indicating that SKI was the cause of the bioactivity in APR. Molecular docking simulations showed corresponding results with highly negative binding energies (−6.59 to −8.72 kcal/mol) predicted for the binding of SKI to PLA2 proteins. An important trend found was the presence of free bound Ca2+ lowered binding energies signifying that Ca2+ a has role in the binding of the SKI to PLA2 proteins. The anti-venom property of APR and the pure compound SKI, upon further studies, could be the first line of defense in the medical protocol of snake venom neutralization.
Keywords: Andrographis paniculata (Burm.f.) Nees, Naja philippinensis Taylor, gas chromatography-electron ionization-mass spectrometry, secretory phospholipase A2, docking and cluster analysis.